Cross-culturally Speaking, Speaking Cross-culturally - Peeters, Bert, 1960-; Mullan, Kerry; Béal, Christine (Cambridge Scholars Publishing, 2013)
Did you know that, to get a job in Australia, it is important to use the right balance of informal and formal language during the interview? Did you know that student advising in Wu Chinese (spoken around Shanghai) is not a face-threatening activity, contrary to general perceptions about the nature of advice giving? Did you know that the use of minimal eye contact and flat intonation by Japanese speakers is interpreted by native English speakers as a lack of interest and willingness to commun ...